2022
DOI: 10.1111/1471-0307.12885
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and probabilistic health risk of polychlorinated biphenyls in cheese samples collected from Tehran, Iran

Abstract: This study focused on the measurement of non‐dioxin‐like polychlorinated biphenyls (NDL‐PCBs) in cheese samples (traditional and commercial cheese) by a modified QuEChERS (quick, easy, cheap, effective, rugged and safe) method by gas chromatography (GC) coupled with triple‐quadrupole (QqQ) tandem mass spectrometry (MS/MS). The recovery of NDL‐PCBs was in the range of 93.22–109.19%, and relative standard deviation (RSD) was in the range of 4.24–9.04%. Also, the limit of detections (LODs) and the limit of quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The QuEChERS method, initially developed by Anastassiades et al for pesticide analysis, has found extensive use in the extraction and purification of organic contaminants from fatty samples, including breast milk. This strategy has been successfully applied to isolate various typical organic pollutants, such as PCBs, PBEDs, OCPs, and OPPs from human breast milk, cows’ milk, cream, cheese, and butter . Thus, to develop an efficient analytical method for OLEMs in breast milk, the QuEChERS strategy was chosen.…”
Section: Resultsmentioning
confidence: 99%
“…The QuEChERS method, initially developed by Anastassiades et al for pesticide analysis, has found extensive use in the extraction and purification of organic contaminants from fatty samples, including breast milk. This strategy has been successfully applied to isolate various typical organic pollutants, such as PCBs, PBEDs, OCPs, and OPPs from human breast milk, cows’ milk, cream, cheese, and butter . Thus, to develop an efficient analytical method for OLEMs in breast milk, the QuEChERS strategy was chosen.…”
Section: Resultsmentioning
confidence: 99%